Textual borrowing and source citation among Iranian masters students of science and engineering - Saadabadi M., Hossein; Abd Samad, Arshad; Omar, Zoharah (Jahan Elm Institute of Higher Education, 2017)
This study was conducted to quantitatively evaluate how Iranian ESL graduate students in science and engineering programs understand and view textual borrowing and source citation as two major sources of unintentional plagiarism. To this end two questions were attempted in this research: 1) how do science and engineering students’ view textual borrowing? 2) how do science and engineering students’ view source citation? Reviewing the research on plagiarism studies turned out that most cases of accusation of plagiarism in academic writings of ESL students stem in a few reasons chief among them borrowing text from other sources and inadequate citation of the texts they borrow. The literature also indicated that the problem is more challenging among graduate students in science and engineering programs.To achieve the objectives of the study, a questionnaire was used to elicit how Iranian ESL graduate students in science and engineering programs in Malaysian universities think of and decide on textual borrowing and source citation practices. A cluster analysis of the results indicated three groups of respondents with regard to their understanding of textual borrowing and source citation. The first group was labeled Poor Academic Practitioners (PAP), who had no idea of or a wrong view of source use. Another group included Normal Academic Practitioners (NAP), who were familiar with the locally accepted norms of source use, and finally, the third group was las labeled Informed Academic Practitioners (IAP) whose members were familiar with the international conventions of writing from sources. Suggestions were then made to use the findings of this research in improving the originality of students’ academic products.